THE POTENTIAL OF WOMEN PARTICIPATION IN ISLAMIC BANKING AND FINANCE: A LEGAL ANALYSIS OF THE BARRIERS AND OPPORTUNITIES - Kadi , Sanaa (International Journal of Islamic Banking and Finance Research, 2025)
Gender disparities persist in the Islamic banking and finance (IBF) sector, with women facing structural barriers to financial inclusion and career advancement. Within contemporary socioeconomic transformations characterized by rising female educational attainment and increased labor market participation to meet familial economic needs, these systemic barriers warrant urgent examination. Despite growing recognition of this issue, the relationship between regulatory frameworks and women’s participation remains underexplored in scholarly literature. This study examines the impact of women’s regulatory and participatory roles on the development of the IBF sector and measures the effectiveness of institutional policies in overcoming gender-based barriers. The research employs legal framework analysis, conducting a comprehensive review of literature, laws, regulations, and policies related to women’s empowerment in the IBF sector. The findings indicate that current regulatory and supervisory guidelines in the IBF sector remain insufficient to address gender-based barriers fully. Despite recent efforts, a need remains to further promote female financial inclusion and gender diversity in career development within the IBF sector through regulatory and supervisory guidelines. The study emphasizes the importance of implementing stronger, gender-inclusive policies to encourage women’s participation and leadership in the IBF sector, while upholding adherence to Sharia principles. By strategically applying foundational principles of justice (adl) within the Maqasid al-Sharia framework, the IBF sector can develop approaches that reconcile traditional financial jurisprudence with contemporary socioeconomic imperatives. Such reforms would simultaneously advance gender equity objectives and strengthen the sector’s alignment with sustainable development goals, while preserving the essential ethical parameters of Islamic finance. JEL Classification Codes: G32, F65, L66, L25, M41.